The European Nucleotide Archive in 2017. Issue Volume 46:Issue D1(2018) (13th November 2017) - Silvester, Nicole; Alako, Blaise; Amid, Clara; Cerdeño-Tarrága, Ana; Clarke, Laura; Cleland, Iain; Harrison, Peter W; Jayathilaka, Suran; Kay, Simon; Keane, Thomas; Leinonen, Rasko; Liu, Xin; et al.
Abstract: For 35 years the European Nucleotide Archive (ENA; https://www.ebi.ac.uk/ena ) has been responsible for making the world's public sequencing data available to the scientific community. Advances in sequencing technology have driven exponential growth in the volume of data to be processed and stored and a substantial broadening of the user community. Here, we outline ENA services and content in 2017 and provide insight into a selection of current key areas of development in ENA driven by challenges arising from the above growth.